The Making of Probiotic Drink (Yoghurt) from Cow’s Milk and Soybean Proportion using Lactobacillus casei and Lactobacillus plantarum (Jurnal Ilmu dan Teknologi Hasil Ternak, 2011)
The objective of current study was to find out the effect of Lactobacillus casei and Lactobacillus plantarum onto cow’s milk and soybean’s milk proportion to yoghurt quality. The results showed that the highest of total lactic acid was combination between Lactobacillus plantarum and soybean milk (45 ml). While the highest pH was combination between Lactobacillus casei and cow’s milk (6.48) and the highest viscosity was combination between Lactobacillus casei and cow’s milk (2.9 cp). Keywords: cow’s milk, soybean’s milk, Lactobacillus casei, Lactobacillus plantarum, yoghurt